Internationalisation of SMEs: Critical Review of Theories and Antecedents - Lakshman, Duleepa; Kumarasinghe, P.J.; Weerasinghe, R.N. (University of Sri Jayewardenepura, 2022)
Scholars have paid close attention to developing several theories for internationalisation of small and medium-sized enterprises. These theories explain the firm strategic directions and the gradual process of international expansion. This theoretical literature review aims at comprehensively examining the wide array of literature relating to theories of SME internationalisation and the antecedents of internationalisation. This study looks at the connections and contrasts between twelve internationalisation theories, discusses their shortcomings and provides theory-based insights to SMEs in understanding the internationalisation process. Further, this paper examines ten different antecedents of SME internationalisation and how various researchers measure the impact of the identified antecedents on internationalisation. According to the literature analysis, it has been identified that the majority of the SME internationalisation studies are done in developed countries. Moreover, most of the internationalisation theories are built in developed countries by observing the behaviour of large firms. Hence, these theories and models may not be sufficient to explain SME success in developing and emerging markets. Furthermore, companies currently use many strategic approaches (such as joint ventures, strategic alliances) to internationalise their operations. As a result, it is argued that the existing internationalisation-based literature and theories are insufficient to explain the internationalisation of SMEs in developing countries.
Keywords: Capabilities; Firm Age; Firm Specific Resources; Firm Size; Internationalisation; Small and Medium Enterprises